1994
DOI: 10.1088/0960-1317/4/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of microfluid systems

Abstract: The dynamic behavior of microfluid devices like miniaturized diaphragm pumps, microvalves and flow channels will be discussed. Special interest is directed to the dynamics of microminiaturized diaphragm pumps. A formalism will be given, which allows the evaluation of the interaction between these pumps and the connected fluid system. The results of the simulation will be compared with transient pressure measurements on pneumatically and electrostatically actuated diaphragm pumps on the millisecond time scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 7 publications
3
52
0
Order By: Relevance
“…In addition, we present a lumpedparameter model to analyze the operation of the peristaltic pump. With the model, the dynamics of peristaltic pumping, not addressed by existing micro pump models, [8][9][10] are appropriately investigated. We consider the dynamics of individual pumping chambers and account for the interactions of such component dynamics by a system representation of the peristaltic pump.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we present a lumpedparameter model to analyze the operation of the peristaltic pump. With the model, the dynamics of peristaltic pumping, not addressed by existing micro pump models, [8][9][10] are appropriately investigated. We consider the dynamics of individual pumping chambers and account for the interactions of such component dynamics by a system representation of the peristaltic pump.…”
Section: Introductionmentioning
confidence: 99%
“…Zengerle and Richter have shown that for incompressible fluids elastic elements of a micropump are characterized by their pressure dependent volume deformation, called the fluid capacitance, and defined in formula (2): with being the fluid density [1]. Therefore, elasticity is modeled as an electrical capacitance.…”
Section: Elasticity Of Structural Elementsmentioning
confidence: 99%
“…Zengerle and Richter have shown in 1994 that micropumps could be modeled using the equivalence between fluidic systems and electrical networks [1]. Bourouina et al have verified and used this method to design a micropump for medical application [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Both the electrodes can be fabricated using silicon technique and bonding of the two wafers with a predefined space for the two electrodes is possible [5,9].…”
Section: Mechanical Micropumpmentioning
confidence: 99%
“…Micropumps differ in actuation mechanism, valve mechanism and fabrication process. Pneumatic [5,9], thermopneumatic [5,10], piezoelectric [11,12,13,14], electrostatic [9], bimetallic [15], shape memory effect [16] and electrothermal [17] are some of the mechanical actuation techniques presented in past. In the nonmechanical actuation technique electrohydrodynamic [8], electroosmotic [8,18], ultrasonic [5,8], magnetohydrodynamic [19] are some of the actuation principles.…”
mentioning
confidence: 99%